THE NEUROHUMORAL EFFECTS OF METOCLOPRAMIDUM - Panchuk, S.N.; Zhukova, V.B.; Bondarenko, I.A.; Pasko, H.N.; Solovjova, I.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Neurohumoral effects of metoclopramidum on 18 healthy volunteers were studied with the help of heart rate variability technology (HRV) under acute pharmacological test conditions. The obtained results indicated that metoclopramidum decreases the total power of neurohumoral regulation (NHR) mostly by depressing sympathetic activity and least -  parasympathetic one. The degree of the preparation effect on HRV indexes was determined by the initial sympathovagal balance of the volunteers. Metoclopramidum did not show the ability to modify the directions of HRV parameter changes in conditions of active tilt test. The preparation effect was limited by more significant deposit decrease of a parasympathetic component  with a shift of autonomic balance towards sympathetic influences. The above effect was not determined by the initial values of sympathovagal balance. The determined individuality of the neuroregulatory systems response to metoclopramidum intake requires its preliminary testing in acute pharmacological test. The optimal management of a patient requires planning of the dose and regimen of a medication intake.